Pengaruh Aplikasi Biokom, Coal Fly-Ash, dan Fungi Pelarut P Terhadap Beberapa Sifat Kimia pada Tanah Gambut yang Ditanami Tanaman Jagung (Zea mays) - Muhammad Syifa; Hairil Ifansyah; Ismed Fachruzi (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2023)
As long as the issues with peat soil, particularly with some of its chemical qualities, can be treated properly, it has the potential to be utilized as agricultural land. Empty oil palm fruit bunches (EFB), which are produced by the size of oil palm farms, can be used to make biochar and EFB compost, which are then combined to create biokom, which can enhance soil structure and increase the availability of phosphorus in peat. Aspergillus oryzae-Tb7 is one of the phosphore solubilizing fungus (FPP) that aid in accelerating the release of accessible P. The byproduct of burning coal in a PLTU that is alkaline by nature and capable of raising soil pH to promote an increase in available P is known as coal fly ash (CFA). The goal of this study's conclusion was to ascertain the impact on the chemical characteristics of maize plants' uptake of P as well as soil pH, CEC, soluble Fe, and available P.A single-component, completely randomized design was used in this study (CRD). The factors A 0, which stood for